2011
DOI: 10.1007/s12032-011-9858-3
|View full text |Cite
|
Sign up to set email alerts
|

Profile of infections and outcome in high-risk febrile neutropenia: experience from a tertiary care cancer center in India

Abstract: Objective of the present study was to describe the profile of infections in febrile neutropenia (FN) in acute leukemia and hematopoietic stem cell transplant (HSCT) with emphasis on response to therapy and outcome. In a prospective, observational single-institutional study, consecutive episodes of high-risk FN were enrolled over a 1½-year period. Uniform antibiotic policy and response criteria were used. Of the 200 episodes enrolled, acute leukemia induction comprised 40.5%, consolidation with high-dose cytara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
29
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 23 publications
9
29
3
Order By: Relevance
“…The centre where the present study was undertaken had reported increasing prevalence of GNB among neutropenic patients with BSI since 2000. Mathur et al in 2002 and Ghosh et al in 2012 reported 47% and 56% GNB respectively among the isolates in their studies [8,9]. However, the present study documented a much higher prevalence of GNB (91%).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The centre where the present study was undertaken had reported increasing prevalence of GNB among neutropenic patients with BSI since 2000. Mathur et al in 2002 and Ghosh et al in 2012 reported 47% and 56% GNB respectively among the isolates in their studies [8,9]. However, the present study documented a much higher prevalence of GNB (91%).…”
Section: Discussioncontrasting
confidence: 61%
“…However, the present study documented a much higher prevalence of GNB (91%). This increase may be attributed to one or more of the following: the discontinuation of fluoroquinolone prophylaxis in our centre, chemotherapy-associated mucositis, use of long term indwelling catheters, and immune defects like neutropenia and lymphocyte dysfunction [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…A similar prospective observational study from our Institute showed an overall mortality rate of 8% (Ghosh et al, 2012). A similar study on febrile neutropenic patients from Thailand showed an overall mortality rate of 14% (Chindaprasirt et al, 2013) while in our cohort it was around 5%.…”
Section: Discussionsupporting
confidence: 72%
“…A similar study on febrile neutropenic patients from Thailand showed an overall mortality rate of 14% (Chindaprasirt et al, 2013) while in our cohort it was around 5%. The above study was done on patients with leukaemia and undergoing hematopoietic stem cell transplantation (Ghosh et al, 2012). The use of antibiotic was uniform in that study and mortality was associated with a nadir leukocyte count <200/μl and an abnormal chest radiograph.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of fungal infection was like studies reported from India. Two cases of invasive aspergillosis was reported in HM, this may be due to construction work carried on during our study period [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%